ANALISIS KAPASITAS SIMPANG SUKUR DAN KINERJA RUAS JALAN MANADO-BITUNG (EXISTING) PASCA PEMBANGUNAN TOLL MANADO-BITUNG (SEGMEN 1) - Untung, Evangelina; Rompis, Semuel Y. R.; Sendow, Theo K. (Sam Ratulangi University, 2018)
The road infrastructure sector is one of the lifebloods in the region's economic growth, so theaccuracy of its provision through the amount of investment is of paramount importance. With regardto economic development, road and bridge investments have a wide influence both for road users and/ or bridges as well as for the region as a whole. Therefore, it is necessary to have the right policies inthe way of the roads so as to support the development of the region and its economic growth.Currently, the construction of road and bridge infrastructure throughout the province of NorthSulawesi is being actively undertaken, including the construction of Manado - Bitung Toll Road, withfunding sources from the State Budget, Loan China as well as funding sources from multiyearcontracted Investors. In accordance with Presidential Regulation No. 56/2011, toll road concessionsmay be undertaken by the Government for economically viable but less financially feasible segments.So with the limitation of pure Government fund and weak domestic fund mobilization, it is necessaryto initiate the development of toll road through bilateral / multirateral loan mechanism. The aims of this research is: To analyze the intersection capacity of the intersection of ManadoBitungatSimpangSukurintwoconditionsbefore(junction3arm)andafteraccessroadofSimpangSusunSukur (Exit Tol Manado - Bitung Segment 1) was built (junction 4 arm), to analyzePerformance of Manado-Bitung Road Area with PKJI 2014 Method and to formulate the necessaryhandling at the Sukur intersection. In this research it were used data collection method (Primary and secondary sampling method). The primary survey is a traffic survey on Manado - Bitung road (eksisting), especially in thelocation of Sukur Intersection in the intersection survey in three approach namely Sukur, Manado andKauditan approach were give proportion of LV(%), HV(%) and MC (%) as follows : 56.5; 1.2; and42.3 for Sukur approach, 5.73; 7.3; and 35.5 for Manado approach and 52.9; 6.2 ; and 40.9 forKauditan respectively. The calculation of the degree of saturation (DS) in observation year (2017)shows that 2/3 of the daytime is greater than 0.75 which means there will be a possibility of traffic(queue) with an opportunity above 70%. From the results of performance analysis on Manado -Bitung roads in 2020 and so on the existing volume has passed the available capacity. By the year2018 VCR has reached 0.82 and this has become a warning for the passengers of the road to open anew road that is Manado - Bitung toll road. The level of service of Manado - Bitung road is in therange of service level D until 2019 and service level E in 2020 and 2021 to F. Sukur - Matungkas roadsegment until the end of 2022 the available volume is still below the available capacity and obtainedservice level of Sukur - Matungkas road is in the range of service level A and B from 2017 to 2022. Keywords: intersection capacity analysis, economic growth, level of service, degree of saturation